Interior design elements for the conservation of Terengganu traditional Malay house - Salem Alqamaz, Salem Saeed
The existence of vernacular architecture in the world, and particularly in Terengganu, Malaysia is under threat because of fast impacts such as modernisation, urbanisation, and socio-economic transformation, loss of its qualities coming from changes and development, and misinterpretation of its typology as well as severe abandonment issues. It is clear that in Malaysia the conservation of heritage appears to be based more on architectural structures than on a comprehensive strategy which incorporates the surrounding environment. The absence of such a strategy has therefore led to the disappearance of the conventional or historical landscape. s of today, the Terengganu traditional Malay houses (TTMH) are slowly being abandoned and are becoming derelict, thereby threatening the survival of the vernacular values of their fabric and the conservation for future generations. This statement is significant as a starting point for this research, as the situation that it outline remains to this day. Thus, the study dealt with the subject of the interior design directly, and it was related to the conserving Terengganu traditional Malay houses, as the study results identified the factors from the study sample perspective. The current research aims to identify the interior design elements for the conservation of TTMH. The study employs a quantitative approach by creating a survey questionnaire that can be used as a broad model and new instrument to help collect data about the design elements and the factors that influence the ch i e of TTMH. The questionnaire survey contains three variables: interior design, cultural heritage and carving and climate. Furthermore, the research method consists of distribution the questionnaire among 384 citizens of Terengganu, and the data were analy ed u ing Factor Analysis and Cluster Analysis statistical Package for social Sciences ( PSS). The results of the study showed the most influential factors on TTMH from each ariable among the interior design of TTMH, carving and climate, and cultural heritage in houses, such as maintain, materials, and skilled. In conclusion, this understanding of the interior design elements in the conservation of the TTMH from the perspectives citizens of Terengganu has identified a niche in the form of needs to be emphasized, and fits with the need for a holistic approach. Furthermore, this research makes a significant contribution in expanding the existing body of knowledge, through the exploration of how the house owners understand, value, and appreciate heritage within their environment, in addition to including research method approach which is quantitative in traditional architecture studies.